2019
DOI: 10.1109/access.2019.2903234
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Power Assist Lifting Device With a Fuzzy PID Speed Regulator

Abstract: This paper introduces the development of a one-degree-of-freedom (1DOF) power assist device that helps to lift objects and facilitate the operator's job. The existing designs were examined for different control approaches and human-robot cooperation intuitiveness. The project involves the mechanical design of the experimental setup and development of advantageous control system. Since a task for the device is highly dependent on the mass of handling object, an adaptive strategy is a major concern of control sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We believe that the mentioned dynamic effects and resulting nonlinear forces may have an impact on the system configurations and performance for force controls, especially the force controls of multi-degree-of-freedom systems. However, these types of dynamic effects are not to be so significant for position controls [21,22,28]. All these factors have favored the position control over its counterparts (force controls).…”
Section: Superiority Of Position Control: the Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the mentioned dynamic effects and resulting nonlinear forces may have an impact on the system configurations and performance for force controls, especially the force controls of multi-degree-of-freedom systems. However, these types of dynamic effects are not to be so significant for position controls [21,22,28]. All these factors have favored the position control over its counterparts (force controls).…”
Section: Superiority Of Position Control: the Reasoningmentioning
confidence: 99%
“…However, such initiatives were not taken. In addition, we posit that an empirically designed weight-perception-based adaptive control strategy added to the top of the position and force control strategies could be able to adapt the effects generated due to the weight perceptual issues [13,28]. However, such efforts were not attempted in [7].…”
Section: Human-friendly Control Strategies For Power Assist Robotic Systems: Position and Force Controlsmentioning
confidence: 99%
“…Fuzzy logic control finds applications in various areas, such as speed control, position control, torque control, robotics, automation, and energy efficiency optimization for DC motors. By enabling precise and adaptive control, it effectively addresses non-linearities and varying operating conditions, providing intelligent control strategies for diverse applications [33,29,27].…”
Section: Introductionmentioning
confidence: 99%
“…A Fuzzy Logic-based Controller (FLC) can overcome these disadvantages [8][9][10]. The FLC does not need the model of the plant, can handle non-linearity, it is less sensitive to load disturbances, it produces human logic linguistic rules, and is robust [11][12][13]. Authors in [14] suggested a 3-phase IM speed control technique using constant V/F control.…”
Section: Introductionmentioning
confidence: 99%